VALIDASI EKSPERIMENTAL LABORATORIUM PERILAKU LENTUR STRUKTUR BALOK BETON SANDWICH TERHADAP PENGARUH TEMPERATUR TINGGI: Experimental Laboratory Validation Flexural Behavior of Sandwich Concrete Beams Under High Temperature Exposure - Affiano, Vembri; Murtiadi, Suryawan; Taufik, Syahril; Akmaluddin, Akmaluddin (Spektrum Sipil, 2025)
Concrete is a primary material widely used in structural elements due to its high compressive strength. However, concrete experiences a significant reduction in compressive strength when exposed to elevated temperatures. This study investigates the flexural behavior of normal and sandwich concrete beams subjected to high temperatures. Numerical modeling using ANSYS software was performed to validate laboratory experimental results. The analysis includes load-bearing capacity, stress distribution based on von Mises criteria, and beam deflection. The models consist of normal concrete and sandwich concrete beams with dimensions of 200×300×4000 mm. The compressive strength of normal concrete is 25 MPa, while the lightweight core concrete in the sandwich beam is 15 MPa, with a concrete cover of 20 mm. Reinforcement consists of 3Ø12 mm tensile bars and 2Ø12 mm compressive bars with a yield strength of 300 MPa. Two-point loads were applied symmetrically at one-third of the span from the supports. The results show that the load capacity of normal concrete beams at 20°C, 200°C, 400°C, 600°C, and 800°C are 18.982 kN, 10.899 kN, 8.361 kN, 5.059 kN, and 2.348 kN, respectively, whereas sandwich beams achieve 25.327 kN, 12.101 kN, 7.349 kN, 5.436 kN, and 3.354 kN. It can be concluded that sandwich concrete beams exhibit superior load-bearing stability at elevated temperatures compared to normal concrete beams. Keywords: Concrete beam, Sandwich, Temperature, Stress, Load Capacity